Prophylaxis against spontaneous bacterial peritonitis: Too much or too little? - Muhammad Dhanani; Aparna Krishnamoorthy; Jody D. Ciolino; Kalpana Gupta; Judith M. Strymish (Cambridge University Press, 2022)
Prophylaxis against spontaneous bacterial peritonitis (SBP) is recommended for select patients with cirrhosis, but long-term antibiotic therapy has risks. We evaluated concordance with guideline recommendations in 179 veterans with cirrhosis; 55% received guideline-concordant management of SBP prophylaxis. Despite stable guideline recommendations since 2012, guideline adherence remains low.